Perceptions toward the Nursing Profession to Predict Attrition Factors among Female Saudi Nursing Students: Implications to Enrolment and Drop-Out - Alshutwi, Dr. Sitah; Alharbi, Malak; Almutairi, Dalal; Alotaibi, Reem (International Journal of Innovative Research in Medical Science, 2021)
Background: The attrition rate among nursing students is a serious phenomenon; however, this issue has attracted such little attention particularly in Saudi Arabia. Objective: This study aimed to assess students’ perceptions toward nursing and the factors and intention that influenced them to drop out from the program. The study also examined the predictors of students’ perceived factors and intention to quit nursing. Design: Quantitative, correlational, and cross-sectional design. Method: A convenience sample of 162 baccalaureate nursing students was surveyed. A logistic regression analysis was implemented to examine the predictor variables on students’ perceived factors and intention to quit nursing. Results: The overall agreement of the perceptions of nursing students toward the nursing profession can be interpreted as positive. In addition, the perceived factors are strong, whereas their intention to quit nursing is low. Nursing students’ age, marital status, and having no children had significant correlations with the factors that cause drop-out from the nursing program. Having a friend or relative who is a nurse and the positive family’s reaction to enrolment to nursing had significant relationships with the low level of intention to quit nursing. The strong and positive agreement with their perceptions of nursing as a profession had predictive effects on the perceived factors that cause dropping out from the nursing program. Conclusions: Female Saudi nursing students had positive perceptions and low intention to quit nursing but strongly agreed with the factors that cause drop-outs. As previous studies showed conflicting views with the current study, a further investigation involving students (males and females) and the public on a national level is paramount to gain a clear view of nursing in the country. Students and public view of nursing can affect and influence high school students who plan to enroll into the nursing program.